LEGAL PROTECTION FOR DRIVER AGAINST CANCELLATION OF FOOD AND BEVERAGE ORDERING AGREEMENT THROUGH ONLINE APPLICATION ACCORDING TO LAW NO. 8 YEAR 1999 - Hasdiana Juwita Bintang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research is to find out legal protection for gojek drivers who experience unilateral order cancellations by consumers when making gofood transactions. One-sided cancellation by the customer is an act against the law. For this reason, drivers can claim rights that have not been fulfilled by the customer in Gofood payments. Problems arising from using the online motorcycle taxi application to buy food and drinks range from inappropriate messages, prices for food and drinks that are different from online applications, up to the problem of orders being canceled unilaterally by consumers. This is a problem, so if it is related to civil matters it is included in an unlawful act.